2020
DOI: 10.7717/peerj.9640
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of epidemiological lectures using peer instruction: focusing on the importance of ConcepTests

Abstract: Background In clinical research, the ability to properly analyze data is a necessary skill that cannot be learned simply by listening to lectures. Interactive classes, such as Peer Instruction (PI), are required to help medical students understand the concept of epidemiology for future valid research. In PI lectures, ConcepTests are conducted to confirm and deepen students’ understanding of the lecture material. Although it is important to evaluate PI lectures, there have been no studies conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Besides, students' conceptual understanding (Gok, 2014;Gok & Gok, 2016;Mitsuhashi, 2020;Versteeg et al, 2019) was found to be improved positively as PI helped students to understand the fundamental concepts through questions and answers on the subject discussed. One of the key factors that influenced the impact of PI on students' conceptual understanding was the effectiveness of the concept (Mitsuhashi, 2020). The concept tests were designed to provide additional insight into students' learning by allowing them to explore essential concepts and exposing typical problems with the topic (Crouch & Mazur, 2001;Mitsuhashi, 2020).…”
Section: Impacts Of Peer Instruction (Pi) At the Tertiary Levelmentioning
confidence: 98%
See 3 more Smart Citations
“…Besides, students' conceptual understanding (Gok, 2014;Gok & Gok, 2016;Mitsuhashi, 2020;Versteeg et al, 2019) was found to be improved positively as PI helped students to understand the fundamental concepts through questions and answers on the subject discussed. One of the key factors that influenced the impact of PI on students' conceptual understanding was the effectiveness of the concept (Mitsuhashi, 2020). The concept tests were designed to provide additional insight into students' learning by allowing them to explore essential concepts and exposing typical problems with the topic (Crouch & Mazur, 2001;Mitsuhashi, 2020).…”
Section: Impacts Of Peer Instruction (Pi) At the Tertiary Levelmentioning
confidence: 98%
“…The ineffectiveness of PI on students' achievement may be attributed to students simply selecting the most frequent response or just changing their ideas depending on the agreement of nearby students, rather than learning through PI (Perez et al, 2010). Besides, students' conceptual understanding (Gok, 2014;Gok & Gok, 2016;Mitsuhashi, 2020;Versteeg et al, 2019) was found to be improved positively as PI helped students to understand the fundamental concepts through questions and answers on the subject discussed. One of the key factors that influenced the impact of PI on students' conceptual understanding was the effectiveness of the concept (Mitsuhashi, 2020).…”
Section: Impacts Of Peer Instruction (Pi) At the Tertiary Levelmentioning
confidence: 99%
See 2 more Smart Citations